PRV-1 Infected Macrophages in Melanized Focal Changes in White Muscle of Atlantic Salmon (Salmo salar) Correlates With a Pro-Inflammatory Environment - Malik, Muhammad Salman; Bjørgen, Håvard; Nyman, Ingvild Berg; Wessel, Øystein; Koppang, Erling Olaf; Dahle, Maria K.; Rimstad, Espen (Frontiers in Immunology, 2021)
Melanised focal changes in white skeletal muscle of farmed Atlantic salmon, “black spots”, is a quality problem affecting on average 20% of slaughtered fish. The spots appear initially as “red spots” characterized by hemorrhages and acute inflammation and progress into black spots characterized by chronic inflammation and abundant pigmented cells. Piscine orthoreovirus 1 (PRV-1) has earlier been found to be associated with macrophages and melano-macrophages in red and black spots. Here we have addressed the inflammatory microenvironment of red and black spots by studying the polarization status of the macrophages and cell mediated immune responses in spots, in both PRV-1 infected and non-infected fish. Samples that had been collected at regular intervals through the seawater production period in a commercial farm were analyzed by multiplex fluorescent in situ hybridization (FISH) and qPCR methods. Detection of abundant inducible nitric oxide synthase (iNOS2) expressing M1-polarized macrophages in red spots demonstrated a pro-inflammatory microenvironment. There was an almost perfect co-localization with the iNOS2 expression and PRV-1 infection. Black spots, on the other side, had few iNOS2 expressing cells, but a relatively high number of arginase-2 expressing anti-inflammatory M2-polarized macrophages containing melanin. The numerous M2-polarized melano-macrophages in black spots indicate an ongoing healing phase. Co-localization of PRV-1 and cells expressing CD8+ and MHC-I suggests a targeted immune response taking place in the spots. Altogether, this study indicates that PRV-1 induces a pro-inflammatory environment that is important for the pathogenesis of the spots. We do not have indication that infection of PRV-1 is the initial causative agent of this condition.